Family Employees and Absenteeism - Jörn Block; Laszlo Goerke; José María Millán; Concepción Román (Institute for the Study of Labor (IZA), 2014)
Work effort varies greatly across employees, as evidenced by substantial differences in absence rates. Moreover, absenteeism causes sizeable output losses. Using data from the European Community Household Panel (ECHP), this paper investigates absence behavior of family employees, i.e. workers who are employed in enterprises owned by a relative. Our estimates indicate that being a family employee instead of a regular employee in the private sector significantly reduces both the probability and duration of absence to a substantial degree.
Keywords: I10; J22; M50; 330; European Community Household Panel; family employees; absenteeism; work effort